Root Canal Re-treatment with Gutta Percha: Techniques Influencing Success - Manal Mohammed Aljamal,; jamelahothman alrasasmah,; nassrahmousa al dahi,; Azhar nasser alkaway,; Gadeer Ali Aleid,; wallaabdulkareem althawab,; noufnawaf alharbi,; Sana Abduallah Almutairi,; Hatim Al Brikeet,; Shuaa fahad alhussan,; Munarh Abdullh Alanazi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Root canal re-treatment is a crucial procedure for addressing persistent or recurrent pathology associated with previously root canal-treated teeth. This comprehensive paper explores the techniques and factors influencing the success of root canal re-treatment involving gutta-percha, a widely used root canal filling material. The objectives of re-treatment, including the removal of existing filling material, thorough disinfection, and three-dimensional obturation, are discussed. Various techniques, such as hand instrumentation, rotary instrumentation, thermoplastic techniques, and solvent-based techniques, are examined, highlighting their advantages and limitations. Factors influencing the success of re-treatment are analyzed, including the presence and size of periapical lesions, tooth type and position, number of treatment visits, patient age, operator experience, quality of obturation, preoperative diagnosis, coronal seal, extraradicular infections, and patient compliance. Considerations for successful re-treatment, such as accurate diagnosis, effective removal of existing filling material, thorough cleaning and shaping, three-dimensional obturation, coronal seal, and follow-up monitoring, are emphasized. The paper also explores emerging trends and future directions, including advancements in imaging, novel disinfection techniques, improvements in gutta-percha properties, regenerative endodontics, and the integration of patient-reported outcome measures and interdisciplinary collaboration.